1998
DOI: 10.1038/31651
|View full text |Cite
|
Sign up to set email alerts
|

Global warming on Triton

Abstract: D. V. Distance measurement and wave dispersion in a Liouville string approach to quantum gravity. Int. J. Mod. Phys. A 12, 607-623 (1997). 18. Amelino-Camelia, G. Limits on the measurability of space-time distances in the semi-classical approximation of quantum gravity. Mod. Phys. Lett.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
72
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(79 citation statements)
references
References 18 publications
6
72
1
Order By: Relevance
“…Neptune's satellite Triton-a body similar to Pluto in size, density, and atmospheric constituentsexperienced a smaller pressure increase 19,20 during 1989-97. Surface-pressure increases on both of these bodies would be driven by regaining vapour-pressure equilibrium in response to small increases in the temperature (,1 K) of nitrogen surface ice.…”
mentioning
confidence: 99%
“…Neptune's satellite Triton-a body similar to Pluto in size, density, and atmospheric constituentsexperienced a smaller pressure increase 19,20 during 1989-97. Surface-pressure increases on both of these bodies would be driven by regaining vapour-pressure equilibrium in response to small increases in the temperature (,1 K) of nitrogen surface ice.…”
mentioning
confidence: 99%
“…However, the signal-to-noise ratios for these data sets are not high, in comparison with those for the Tr148 and Tr180 occultations, which involved brighter stars and larger telescopes. In both of these other occultations, the atmosphere exhibited the same temperature and pressure at all points probed to the noise limit of the light curves within these data sets , Elliot et al 1998, 2000. The sub-occultation locations on Triton that were probed by this occultation are given in Table X.…”
Section: Light-curve Analysismentioning
confidence: 98%
“…Following our observations of the Tr176 occultation, Elliot et al (1998) reported Hubble Space Telescope observations of a subsequent occultation by Triton of the star Tr180, which occurred on 1997 November 4 (McDonald and Elliot 1995). They found that the surface pressure of Triton's atmosphere has increased since the time of Voyager, indicating a warming of the N 2 surface frost.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the lifetime of Triton, a 6-m-thick layer of sediments of hydrocarbons (Cruikshank et al 1993) may have been formed by the accumulation of the same kind of molecules that participated in the origin of life in the Earth more than 4 Gyr ago. Triton is the coldest body in the Solar System, with a mean temperature of 38 K, maintained constant by the sublimation and condensation of nitrogen (Elliot et al 1998). Nevertheless, it may harbour an inner ocean, hidden at a depth of about 100 km under the nitrogen-ice surface.…”
Section: Triton and The Neptunian Systemmentioning
confidence: 99%